Recent stagnation period and unprecedented deoxygenation in the Baltic Sea: causes and consequences - Liblik, Taavi; Siht, Enriko; Buschmann, Fred; Kaljumäe, Marlene; Kikas, Villu; Lips, Urmas; Luik, Stella-Theresa; Maslova, Diana; Pärt, Kristian; Salm, Kai; Samlas, Oliver; Siiriä, Simo-Matti; et al. (Frontiers in Earth Science, 2025)
The properties of the Baltic Sea deep waters are strongly influenced by the alternation between Major Baltic Inflows (MBIs) and the stagnation periods separating them. In the present observation-based study, we report developments in the Central Baltic Sea during the last stagnation period from 2016 to 2024 in the context of changes since the 1960s. There has been a trend towards enhanced oxygen deficiency at the end of consecutive stagnation periods since the late 1960s, with a decline rate of 1.5 μmol L−1 y−1 in the volume-averaged oxygen concentration below 100 m depth in the Eastern Gotland Basin (EGB). The magnitude of deoxygenation in the latest stagnation period remarkably deviates from this trend toward more severe deficiency. The oxygen deficit below 100 m in the EGB was 2.5 106 t in 2024, which is approximately double compared to the end of the last stagnation in 2013. The current high oxygen deficit is accompanied by high ammonium and phosphate concentrations and unusually warm water in the deep layer. We suggest that the reasons behind the current extensive oxygen deficiency are, besides long-term eutrophication, a dense bottom layer, strong and extended stratification hindering vertical oxygen import, weak horizontal oxygen transport, and higher water temperature affecting oxygen solubility and organic matter mineralization rates. The mentioned factors are likely connected to the overall warming of the Baltic and North Sea and can be attributed to climate change. Our results suggest that, under the current anthropogenic pressure, existing internal phosphorus load and with warmer water due to climate change, it is highly unlikely that deoxygenation will be alleviated in the Baltic Sea over the coming decade.